An analysis of socioeconomic factors on multiple chronic conditions and its economic burden: evidence from the National Health Service Survey in Yunnan Province, China - Peng, Puxian; Li, Jing; Wang, Liping; Ai, Zhonghua; Tang, Churou; Tang, Songyuan (Frontiers in Public Health, 2023)
Background: The economic burden of multiple chronic conditions (MCCs) and its socio-economic influencing factors have widely raised public concerns. However, there are few large population-based studies on these problems in China. Our study aims at determining the economic burden of MCCs and associated factors specific to multimorbidity among middle-aged and older individuals. Methods: As our study population, we extracted all 11304 participants over 35 years old from the 2018 National Health Service Survey (NHSS) in Yunnan. Economic burden and socio-demographic characteristics were analyzed with descriptive statistics. Chi-square test and Generalized Estimating Equations (GEE) regression models were used to identify influencing factors. Results: The prevalence of chronic diseases was 35.93% in 11304 participants and the prevalence of MCCs increased with age, was 10.12%. Residents who lived in rural areas were more likely to report MCCs than those who lived in urban areas (adjusted OR=1.347, 97.5% CI: 1.116–1.626). Ethnic minority groups were less likely to report MCCs than those of Han (OR=0.752, 97.5% CI: 0.601–0.942). Overweight or obese people were more likely to report MCCs than people with normal weight (OR=1.317, 97.5% CI: 1.099-1.579). The per capita expenses of two weeks’ illness, per capita hospitalization expenses, annual household income, annual household expenses, and annual household medical expenses of MCCs were ¥292.90 (±1427.80), ¥4804.22 (±11851.63), ¥51064.77 (±52158.76), ¥41933.50 (±39940.02) and ¥11724.94 (±11642.74), respectively. The per capita expenses of two weeks’ illness, per capita hospitalization expenses, annual household income, annual household cost, and annual household medical expenses of hypertensive co-diabetic patients were more compared to those with other three comorbidity modes. Conclusions: The prevalence of MCCs was relatively high among middle-aged and older individuals in Yunnan, China, which bought a heavy economic burden. This encourages policy makers and health providers to pay more attention to the behavioral/lifestyle factors, that contribute to multimorbidity to a great extent. Furthermore, health promotion and education in terms of MCCs need to be prioritized in Yunnan.